PREVENTION OF SUBCLINICAL KETOSIS IN DAIRY COWS (Conferencea, 2023)
This article describes the means of prevention of subclinical ketosis in cows, their effect on clinical and hematological parameters. In the prevention of subclinical ketosis in productive cows, LPP-1 vitamin-mineral premix 40 g per head per day, 1.5 g of sodium bicarbonate per head, 20 g of sodium bicarbonate per head per day, and the effectiveness of giving it in the 1-3 months of lactation are high. improves and increases the functional state of metabolism and liver and prevents subclinical ketosis.